Unbinding of surface defects under the defect-selective adsorption - Vakarin, E.V. (Condensed Matter Physics, 2003)
Unbinding of surface topological defects in the presence of the defectselective
adsorption is investigated using a coupled Coulomb Gas – Lattice
Gas model. The unbinding temperature increases with the increasing
selectivity (and coverage) for both, sign-dependent and sign-independent
adsorption. In the latter case, the adsorbates tend to increase the number
density of defects. The stability requirement implies that the adsorbate
cluster size must be coherent with the screening length of free defects Досліджується вивільнення поверхневих дефектів при дефектно-селективній адсорбції, використовуючи комбінацію моделей ґраткового газу і кулонівського газу. Температура вивільнення зростає з ростом селективності як для знако-залежної, так і для знако-незалежної
адсорбції. В останньому випадку адсорбат збільшує густину дефектів. Вимога стабільності вказує на те, що розмір кластера в адсорбаті має бути співмірним з довжиною екранування вільних дефектів.